‘They Were Talking to Each Other but Not to Me’: Examining the Drivers of Patients' Poor Experiences During the Transition From the Hospital to Skilled Nursing Facility - James D. Harrison; Margaret C. Fang; Rebecca L. Sudore; Andrew D. Auerbach; Tasce Bongiovanni; Audrey Lyndon (Health Expectations, 2025)
ABSTRACT Introduction Hospital‐to‐skilled nursing facility (SNF) transitions have been characterised as fragmented and having poor quality. The drivers, or the factors and actions, that directly lead to these poor experiences are not well described. It is essential to understand the drivers of these experiences so that specific improvement targets can be identified. This study aimed to generate a theory of contributing factors that determine patient and caregiver experiences during the transition from the hospital to SNF. Methods We conducted a grounded theory study on the Medicine Service at an academic medical centre (AMC) and a short‐term rehabilitation SNF. We conducted individual in‐depth interviews with patients, caregivers and clinicians, as well as ethnographic observations of hospital and SNF care activities. We analysed data using dimensional analysis to create an explanatory matrix that identified prominent dimensions and considered the context, conditions and processes that result in patient and caregiver consequences and experiences. Results We completed 41 interviews (15 patients, 5 caregivers and 15 AMC and 6 SNF clinicians) and 40 h of ethnographic observations. ‘They were talking to each other, but not to me’ was the dimension with the greatest explanatory power regarding patient and caregiver experience. Patients and caregivers consistently felt disconnected from their care teams and lacked sufficient information leading to uncertainty about their SNF admission and plans for recovery. Key conditions driving these outcomes were patient and care team processes, including interdisciplinary team‐based care, clinical training and practice norms, pressure to maintain hospital throughput, patient behaviours, the availability and provision of information, and patient's physical and emotional vulnerability. The relationships between conditions and processes were complex, dynamic and, at times, interrelated. Conclusion This study has conceptualised the root causes of poor‐quality experiences within the hospital‐to‐SNF care transition. Our theory generation identifies targets for clinical practice improvement, tailored intervention development and medical education innovations. Patient or Public Contribution We partnered with the Hospital Medicine Reengineering Network (HOMERuN) Patient and Family Advisory Council during all stages of this study.